MENINGKATKAN KEPERCAYAAN DIRI SISWA DALAM BERINTERAKSI SOSIAL DENGAN KONSELING KELOMPOK RATIONAL EMOTIVE BEHAVIOR THERAPY: LITERATURE REVIEW - Tri Ulviani; Netrawati; Yeni Karneli (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Adolescence is a transitional period to build student identity and develop a self-assessment mindset. Adolescent developmental tasks require significant changes in attitudes and behavior patterns. Due to the developmental tasks of adolescence describing the extent of changes that must be made and the problems that arise from the changes themselves, adolescence is often a difficult problem to solve. Lack of confidence in social interaction is one of the obstacles in changing attitudes and behavior. As a result, students who lack confidence in the social environment often do not have friends, are alone, and have difficulty adjusting to their environment. Students who lack self-confidence have more difficulty growing and developing in the activities they participate in at home, at school, and in the community. This writing uses a literature review and literature study by exploring various literature related to self-confidence in social interaction and group counseling approaches to rational emotive behavior therapy. Group counseling utilizes the dynamics of group members in the service process. The stages in the REBT counseling approach are using the ABC theory.